Bush encroachment and invasive alien plant species’ linkage to outmigration - Solomon W. Newete; George J. Chirima; Richard Tswai (Discover Sustainability)
Abstract The most prominent drivers of international migration across borders and internal migration-rural to urban areas are explained by the ‘push and pull’ migration model. However, this model falls short in addressing migrations driven by the impacts of climate change, such as the movement from rural to urban area as a coping strategy for environmental degradation. Factors like deforestation, desertification, droughts, and floods are key drivers of such migration. Additionally, bush encroachment and the spread of invasive alien plant species disrupt landscapes and negatively affect ecosystem goods and services in many arid and semi-arid regions around the world. This phenomenon directly affects the livelihoods of rural communities by depriving them of their croplands, rangelands, and ranches. Despite this, there is a lack of sufficient information on how these factors are linked to migratory movements, whether from rural to urban areas or between rural regions. To explore this connection, this study reviewed scientific publications, including journal articles and books using key phrases such as, ‘push and pull migration factors’, ‘impact of bush encroachment on migration’ and ‘impact of invasive alien plants on migration factors’, among others. A total of 155 documents were downloaded via Google Scholar, of which 99 were thoroughly reviewed and included in the study. The remaining 53 documents were skimmed and excluded due to their irrelevance, or limited contribution to the research. The study found that the bush encroachment and invasive plant species in rangelands are significant push factors for driving migration, both between rural areas and rural to urban areas. It is, therefore, recommended that these two factors be given a greater attention when addressing outmigration from rural regions.